2007
DOI: 10.1159/000106325
|View full text |Cite
|
Sign up to set email alerts
|

Does Lower-Pole Caliceal Anatomy Predict Stone Clearance after Shock Wave Lithotripsy for Primary Lower-Pole Nephrolithiasis?

Abstract: Aim: In order to have an idea about the success rates after extracorporeal shock wave lithotripsy (SWL) in patients with lower-pole stones, we reviewed the caliceal anatomy of the patients treated in our clinic. Patients and Methods: One hundred and ninety-eight patients having at least a 3-month follow-up period, with a single stone located in the lower pole, were included. Lower infundibulopelvic angle (LIP-A), infundibular width, and infundibular length were measured from standard intravenous urograms taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Another limitation was in evaluating children; no standard imaging was used and CT was avoided because of the potential risk that was discussed above. As it was reported, many factors such as calyceal anatomy, lower infundibulopelvic angle, infundibular length and diameter, could be predictive of stone-free rates for calyceal stones, which were all overlooked in that study (21)(22)(23). Finally, it was a retrospective study and some data could not be retrieved from several centers.…”
Section: Discussionmentioning
confidence: 92%
“…Another limitation was in evaluating children; no standard imaging was used and CT was avoided because of the potential risk that was discussed above. As it was reported, many factors such as calyceal anatomy, lower infundibulopelvic angle, infundibular length and diameter, could be predictive of stone-free rates for calyceal stones, which were all overlooked in that study (21)(22)(23). Finally, it was a retrospective study and some data could not be retrieved from several centers.…”
Section: Discussionmentioning
confidence: 92%
“…In the study conducted by Talas et al on 198 patients, the IA was reported to be one of the essential factors in the removal of residual stone fragments after SWL in lower calyx kidney stones. 17 In the retrospective study conducted by Viswaroop et al on 148 patients, it was revealed that the IA did not have a significant relationship with the success of treatment in the lower calyx stones 10 mm and above. 18 Similarly, our results yielded that the IA did not affect SWL success.…”
Section: Discussionmentioning
confidence: 92%
“…On multivariate analysis, it was found that stone multiplicity, stone location and HU were independent significant predictors for the treatments after SWL (p values < 0.05) (Table 2). Table 3 summarizes SWL contemporary series tracking the required auxiliary procedures after SWL and predictors of SWL failure (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%